A Review on Travel and Tourism System - Agarwal, Pranav; Singh, Harkirat; Saini, Anurag (Journal of Advanced Research in Information Technology, Systems and Management, 2022)
Travel has been one of the major growing industries right now. Starting from the time of depending upon the local reviews to travel, to now knowing about various travel destination in the blink of an eye, internet helped a lot in the industry. Various research papers have also been published in order to detail out more about the possibilities of the technology for the tourism industry. However, it has also been noticed that there could be some internet related issues as well in the tourism, which are also often researched upon. E-business is another opportunity in the tourism sector. How to cite this article: Agarwal P, Singh H, Saini A. A Review on Travel and Tourism System. J Adv Res Info Tech Sys Mgmt 2022; 6(1): 5-8.